The effect of intellectual capital on financial performance in non-cyclical consumer sector companies listed in IDX - Iroth, Randa Matthew; Budiarso, Novi Swandari; Rondonuwu, Sintje (Journal of Contemporary Accounting, 2023)
The purpose of this study was to determine the effect of intellectual capital on financial performance. Intellectual capital is proxied by 3 variables namely human capital, structural capital, and customer capital on financial performance which is proxied by ROA. There were 30 sample companies selected from 87 companies in the consumer non-cyclical sector with observational data for the 2019-2022 period. The research used is a type of quantitative research and uses a purposive sampling method. The data analysis technique in this study was used multiple linear regression. The results of this study partially show that human capital significant effect on financial performance, structural capital significant effect on financial performance, and customer capital significant effect on financial performance. The results of the study simultaneously show that human capital, structural capital and customer capital has an effecton financial performance.